A simple procedure for fault detectors design in SISO systems. (March 2020) - Tena, D.; Peñarrocha-Alós, I.
Abstract: In this work, we present a novel approach for fault detectors design and implementation in the case of actuator faults. Both the design and the implementation are focused on simplicity. The fault detector is based in an output observer that estimates the fault signal followed by a decision mechanism that detects the presence of a fault from the estimation. The observer consists of two transfer functions fed by the process manipulated variable and the sensor measurement. For the synthesis of the fault detector, we just need an input–output model of the process and two tuning parameters; one used in the observer, and the other in the decision mechanism. We present simple rules for the design considering the trade-off between the detection time, the minimum detectable fault and the false alarm rate. Our implementation method uses standard tools available in industrial control systems and we have applied it to a real two-tank system setup. The main contribution of this work is the simplicity of the design and implementation of the fault detector, making it suitable for process industry and for being managed by not experts in control systems. Another contribution is the a priori design based in intuitive engineering performance indices. Highlights: A fault detector based in input–output models improving the method understanding. Design based on false alarm rate, minimum detectable fault and detection time. Tuning rules based in the process model involving just three parameters. Easy implementation technique, using tools from industrial control systems.